Quantitative Analysis of the Macular and Peripapillary Capillary Network with Optical Coherence Tomography Angiography in Chinese Adolescents: The Tuyou County Pediatric Eye (TYPE) Study - Yang, Yajun (Int J Gen Med, 2021)
AIM: To use OCTA to collect normative data describing the vascular perfusion of the macula and optic disc in adolescents. METHODS: This cross-sectional, school-based study was conducted from Oct 15, 2019, to Nov 30, 2019, in Tuyou County, Baotou, China. All eligible participants underwent a comprehensive questionnaire and ocular examination. The vascular perfusion of the macula and optic disc was determined using a spectral-domain OCTA device. RESULTS: A total of 570 anatomically normal eyes without a history of pathologic disease from 570 adolescents (mean ± SD age, 15.1 ± 1.9 years; 298 girls [52.3%]) were enrolled. In the macula, the mean ± SD perifoveal perfusion density (PD) of the superficial capillary plexus (SCP) and deep capillary plexus (DCP) was 44.2% ± 4.37% and 50.74% ± 3.98%, respectively. The mean ± SD foveal avascular zone (FAZ) was 0.32 mm(2) ± 0.11 mm(2). The mean ± SD peripapillary vessel density (PVD) was 54.98% ± 3.53%. The inferior hemiretinal SCP-PD, DCP-PD, FAZ, and PVD was larger in girls than boys (P = 0.006, P = 0.001, P < 0.001, and P = 0.006, respectively) Multiple regression analysis confirmed that sex independently affected the DCP-PD, FAZ, and PVD (P < 0.001, P < 0.001, and P = 0.029, respectively) and that axial length (AL) independently affected the FAZ area and PVD (P = 0.004 and P < 0.001, respectively). CONCLUSION: Quantitative studies of the perifoveal vasculature in adolescents should consider the patient’s sex and AL. Our findings may provide useful information for the understanding and the management of retinal perfusion in Chinese adolescents.